Convenience store visits by US adolescents: Rationale for healthier retail environments - Sanders-Jackson, Ashley (Health Place, 2015)
Given interest in the public health impact of convenience stores, it is surprising that so little is known about the popularity of these destinations for youth. We surveyed 2,772 adolescents (age 13–16) from a nationally representative web panel of US households. Nearly half (47.5%) of adolescents reported visiting convenience stores at least weekly. Significant risk factors for frequent visits were age, being African American, living in rural areas and in areas with higher levels of neighborhood deprivation. With approximately 4.1 million US adolescents visiting convenience stores at least weekly, new policies and other interventions are needed to promote a healthier retail environment for youth.